Дослідження структурно-механічних властивостей тіста з гречаним борошном - Михонік, Лариса Анатоліївна; Гетьман, Інна Анатоліївна; Погорєлов, Іван Сергійович (My University, 2024)
У статті наведено результати досліджень структурно-механічних характеристик тіста з пшеничного борошна з додаванням борошна зеленої і темної гречки. За допомогою фаринографа та альвеографа було визначено водопоглинальну здатність, стійкість, тривалість утворення, еластичність, пружність, розтяжність, розрідження тіста. Визначено формоутримувальну та газоутримувальну здатності тіста. Встановлено, що борошно зеленої гречки в меншій мірі впливає на реологічні характеристики тіста, ніж борошно темної гречки. Отримані результати є підґрунтям для розробки технологічних заходів для покращення якості хліба з додаванням гречаного борошна. The article provides an analytical review of the use of buckwheat flour in the technology of bakery products. It is shown that the use of this raw material will improve the amino acid, mineral and vitamin composition of the products, will help to increase the content of food fibers in them and reduce the glycemic index, will help to expand the assortment of health products. Today, there are two types of buckwheat flour on the market — from green and dark buck- wheat. Green buckwheat flour is made from thermally unprocessed groats, so it maximally preserves the entire range of macro- and micronutrients, biologically active substances. The use of flour from dark and green buckwheat in the baking industry requires the study of the technological properties of this raw material, including the rheological characteristics of the dough with it. The purpose of re- search, selected materials and research methods are formulated in the article. The results of a set of studies on the study of the structural and mechanical characteristics of wheat flour dough with the addition of 20% of dark and green buckwheat flour are presented. With the help of a farinograph and alveograph, it was established that the addition of buckwheat flour increases the water absorption capacity and duration of dough formation, increases its thinning, elasticity and reduces extensibility, but at the same time its stability increases. The rheological characteristics of the dough with green buckwheat flour, namely its specific volume, duration of formation, stability, elasticity, P/L ratio, expansion index (G) are close to the corresponding values of the control sample, which indicates a smal- ler negative effect of this flour on the structural — mechanical pro- perties of the dough. The study of the shape-retaining and gas-retaining abilities sho- wed that dough blanks with green buckwheat flour will have a larger volume than blanks with dark buckwheat flour, but at the same time they will fall and lose their shape faster. Further research should be directed to the study of the influence of buckwheat flour on the course of the technological process and the quality of products in order to develop technological recom- mendations and optimal recipes for obtaining products with high consumer properties.
Keywords: борошно; зелена гречка; структурно-механічні властивості; хлібобулочні вироби; flour; green buckwheat; structural and mechanical properties; bakery products; кафедра технології хлібопекарських і кондитерських виробів